Autonomía(s) e interculturalidad en un modelo de gestión cultural “otro” - Robles Rivera, Francisco (2010)
Mainly, this model seeks the rupture of “the monopolic and totalizing culture” and in that way, to guarantee not only intercultural dialogues but also our own acquisition of realities and contexts coming from the cultural managers, with the purpose of being able to transform them.